Continue Your Fight for Hungary - Héderváry, Claire de (1959)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Collegiate Society of Hungarian Veterans Emotional appeal to Sir Leslie Munro to continue his fight for Hungary in front of the General Assembly with determination, and stressing the truth and the ideals of liberty.